Advanced process parameter optimization for dimensional accuracy in SS 316L 3D printing using response surface methodology - Venkata Phani Babu Vemuri; Veeresh Kumar Gonal Basavaraja; Ravikiran Chinthalapudi; Bridjesh Pappula (Materials Research Express)
This study investigates the enhancement of process parameters to produce SS 316L components employing the EOS M 290, 3D printing machine adapting Direct Metal Laser Sintering (DMLS) technique. An extensive examination was performed using grey relational grade and response surface methodology to determine the best configurations for scan speed, laser power, and layer thickness to enhance the dimensional accuracy as well as overall excellence of the printed components. The Global Performance 7.10.7 CNC coordinate measuring machine was used to check how accurate the dimensions were. The study showed that these factors were very important, and the best settings were found to be 332.017 W for the laser power, 834.617 mm sec ^−1 for the scanning speed, and 75.0673 micrometers for the layer thickness. Contour and overlay plots were used as visualization means to explain the parameter effects and best performance regions. The results highlight the significance to get a proper balance of the energy input and scanning speed in order to be certain of sufficient fusion and cohesion of powder particles while remaining below reasonable construction time limits. The results of this study are significant for improving the quality, accuracy, effectiveness, and reliability of the DMLS process, which will enhance the production of high-quality metal parts in the field of additive manufacturing.